Involvement of abscisic acid and ethylene in the responses of citrus seedlings to salt shock - Gómez-Cadenas, Aurelio; Tadeo, Francisco R.; Primo-Millo, Eduardo; Talón, Manuel (2017)
The responses of salt-sensitive citrus rootstocks to 200 mM NaCl were periodically determined on seedlings of citrange Carrizo (Citrus sinensis [L.] Osbeck x Poncirus trifoliata [L.] Raf) during 30 days. The stressed seedlings adjusted osmotically, reduced stomatal conductance, increased proline content and ethylene production, and showed massive leaf abscission (92%). The salt shock also increased abscisic acid (ABA) and aminocyclopropane-1-carboxylic acid (ACC) in roots, xylem fluid and leaves, and in addition promoted Cl- accumulation. The pattern of change of ABA, ACC and proline followed a two-phase response: an initial transient increase (10-12 days) overlapping with a gradual and continuous accumulation. This biphasic response appears to be compatible with the proposal that the transitory hormonal rises are induced by the osmotic component of salinity, whereas the Cl- increase determines the subsequent accumulations. During the second phase, Cl- levels correlated with abscission in leaves. Production of leaf ethylene was also concomitant with the increase in the abscission rate. Salt-induced abscission was either reduced with CoCl2 (52%) or inhibited with silver thiosulphate (14%). The results suggest that in salt-stressed citrus, leaf abscission is induced by the chloride build-up through a mechanism that stimulates leaf ACC synthesis and further conversion to ethylene.